ANALYSIS OF PRODUCT QUALITY, PRICE, AND LOCATION TOWARDS PURCHASE DECISIONS AT OFFICE OFFICES OF SMALL AND MEDIUM BUSINESS COOPERATIVES IN MEDAN CITY - M. Zulfikri; Miftah El Fikri; Ramadhan Harahap; Dewi Nurmasari Pane; Rizal Ahmad (Universitas Negeri Medan, 2021)
The Medan City Small and Medium Enterprises Cooperatives Office is one of the regional apparatuses in Medan in carrying out government tasks and affairs in the field of cooperative management and small and medium businesses with the scope of work helping the Mayor of Medan. The problem faced is high competition between cooperative and non-cooperative participants who are external rivals, the low number of visitors or consumers who come to the Medan City Small and Medium Enterprises Cooperative Service Office. As well as product quality and location needs to be reviewed. This study aims to determine the effect of Product Quality, Price and Location on Purchasing Decisions at the Medan City Small and Medium Enterprises Cooperative Service Office. Data collection by distributing questionnaires to a sample of 75 respondents. The model is used with Multiple Regression and is processed through SPSS Ver, 22.0. The results showed that the Product Quality, Price, and Location respectively had a significant effect on Purchasing Decisions. Product Quality, Price, and Location Simultaneously have a significant effect on Purchasing Decisions. Adjusted R. Sguare, 0.843 or 84.3%, namely Product Quality, Price, and Location of 84.3% and the composition is explained by other factors.